PERLINDUNGAN HUKUM DIREKSI DAN PEMEGANG SAHAM DALAM PEMBUBARAN PERSEROAN TERBATAS TIDAK AKTIF DITINJAU DARI PUTUSAN MAHKAMAH AGUNG NO 1618 K/PDT/2016 - Aprilia, Jessica; Syukri, Wildan; Ekklesia, Anggraini; Maria, Chindy; Hidayah, Nur; Adawiyah, Rabiatul; Alhasni, Almaidah; Damaiyanti, Tri (Universitas 17 Agustus 1945 Samarinda, 2025)
This article discusses the legal analysis of the dissolution of an inactive Limited Liability Company (PT) by highlighting Supreme Court Decision Number 1618 K/PDT/2016 as the main focus. The main focus of the study is how the decision strengthens legal certainty and protection of the rights of the parties in the process of dissolving a PT that no longer carries out business activities. In practice, there are many PTs that no longer carry out business activities, but are still legally registered, causing uncertainty for both internal and external parties. The Supreme Court's decision is an important reference in determining whether an inactive PT can be dissolved through a legal mechanism without the decision of the General Meeting of Shareholders (GMS). This research uses normative juridical method with legislative approach and decision study. The results of the analysis show that the decision provides a positive precedent in ensuring legal certainty for the parties involved in the dissolution of an inactive PT, and emphasizes that dissolution can be carried out through the court if the legal requirements are met. In addition, legal protection for directors and shareholders is maintained as long as the dissolution process is carried out in accordance with applicable legal procedures. Thus, this decision strengthens the role of the court in maintaining orderly corporate administration and protecting the legal interests of the parties.